Roseomonas harenae sp. nov., from desert gravel soil. Issue 11 (16th November 2020) - Deng, Yang; Sun, Ye; Wang, Hao; Yu, Li-Yan; Zhang, Yu-Qin
Abstract : A Gram-stain-negative, aerobic, non-motile, pink-pigmented, coccus bacterium, designated CPCC 101081 T, was isolated from a gravel soil sample collected from Badain Jara desert, PR China. Growth of the isolate occurred at 10–37 °C and pH 5.0–8.0, with optimal growth at 28–32 °C and pH 7.0, respectively. The major cellular fatty acids were summed feature 8 (C18:1 ω7 c /C 18:1 ω6 c ), summed feature 3 (C 16:1 ω6 c /C16:1 ω7 c ) and C18:1 2-OH. Q-10 was detected as the main respiratory quinone. Diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylcholine, an unidentified phospholipid, an amino-containing lipid and an unidentified glycophospholipid were examined in the polar lipids extraction. The 16S rRNA gene sequence comparison of strain CPCC 101081 T with the available sequences in the GenBank database showed that the isolate was closely related to members of the genus Rosenomonas, with the highest similarity to Roseomonas rosea DSM 14916 T (97.4 %). In the phylogenetic trees based on 16S rRNA gene sequences and the core genomes, strain CPCC 101081 T was included within the clade of the genus Roseomonas, representing a species level, with the closest neighbor of R. rosea DSM 14916 T . The genomic DNA G+C content was 68.7 mol%. The average nucleotide identity and the digital DNA–DNA hybridization values between strain CPCC 101081 T and the related type strains of the genus Roseomonas were all far lower than the cut-off values for definition species. On the basis of above phenotypic and genotypic characteristics, strain CPCC 101081 T is proposed to represent a novel species of the genus Roseomonas with the name Roseomonas harenae sp. nov. strain CPCC 101081 T (=KCTC 62852 T =NBRC 113512 T ) is the type strain of the species.